TANTANGAN PONDOK PESANTREN PADA MASA PANDEMI COVID-19 - Ihin Solihin; Ahmad Jaelani; Nurwadjah Ahmad E.Q.; Andewi Suhartini (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2022)
This study aims to determine the challenges of the As-Syafi'iyah Islamic Boarding School in Pulo Air Sukabumi during the Covid-19 Pandemic. This research uses a qualitative approach in the form of a case study. Data were collected by using observation, interview, field observation, and document study techniques. The validity of the data was obtained through triangulation and referential adequacy. Data analysis was carried out by data reduction, data presentation, and verification. The results of the study revealed that the Pulo Air Sukabumi Islamic Boarding School took several appropriate steps in dealing with these challenges, including equating perceptions among Foundation management, implementing budget efficiency, conducting education and training for teachers/clerics in the field of online technology application skills, preparing hardware and shower. needed for online and offline learning, motivating all existing personnel to do something best for the benefit of the pesantren to survive during this pandemic.